Depression and Fatigue of Breast Cancer Patients Receiving Chemotherapy during the Covid-19 - Dwi Retnaningsih; Roudhotul Auliyak; Mariyati Mariyati; Enggar Nurnaningsih (Indonesian Journal of Global Health Research, 2021)
Depression in breast cancer patients includes mental shock, inability to accept reality, hopelessness, fear of death, and fear of the future. Depression creates long periods of sadness and worry, usually accompanied by feelings of worthlessness. Fatigue is a symptom that often appears in cancer patients undergoing chemotherapy. Associated with the conditions of the COVID-19 pandemic, cancer patients have an increased risk of transmitting COVID-19 because they have decreased endurance. This study aims to determine the relationship between depression and fatigue in breast cancer patients undergoing chemotherapy at Hospital Sultan Agung Semarang Indonesia. The instruments used in this study were questionnaire of the hospitals anxiety and Depression Scale (HADS) and questionnaire of fatigue, 30 female respondents who suffer from breast cancer and have undergone chemotherapy. Rank Spearman data analysis. P value = 0.000 and correlation coefficient value r = 0.671. There is a relationship between depression and fatigue in breast cancer patients undergoing chemotherapy which has an impact on adherence to chemotherapy for breast cancer patients. The higher the level of depression is, the more severe the level of fatigue in cancer patients.